Clarissa's ciphers : meaning & disruption in Richardson's "Clarissa" - Castle, Terry (Cornell University Press, 1982)
"As Samuel Richardson's 'exemplar to her sex', Clarissa in the eponymous novel published in 1748 is the paradigmatic female victim. In Clarissa's Ciphers, Terry Castle delineates the ways in which, in a world where only voice carries authority, Clarissa is repeatedly silenced, both metaphorically and literally. A victim of rape, she is first a victim of hermeneutic abuse. Drawing on feminist criticism and hermeneutic theory, Castle examines the question of authority in the novel. By tracing the patterns of abuse and exploitation that occur when meanings are arbitrarily and violently imposed, she explores the sexual politics of reading."--Provided by publisher